Market Systems and Buddhist Philosophy: A Holistic Approach to Economic Development - Adhikari, Jyoti (Journal of Buddhist Studies (T.U.), 2025)
This study integrates early Buddhist notions, mainly Dependent Origination (Pratītyasamutpāda) and Hetu Pratyaya (particular conditionality), to present an interdisciplinary, holistic paradigm for Market Systems Development (MSD). Traditional market analysis frequently prioritizes technical or economic issues over ethical and relational aspects. This study connects philosophical ideas with development practice by utilizing two empirical case studies (Ethiopia's Feed the Future-MSD and Mozambique's REDI) as well as doctrinal analysis of important Buddhist texts. The fundamental components of MSD, market exchanges, supporting roles, and unwritten laws and conventions are reinterpreted through the operationalization of Buddhist concepts like clinging, impermanence, and Kamma (ethical causation). We find flaws in the dominant MSD frameworks, such as a propensity to emphasize proximate limitations, inadequate feedback analysis, and a deficiency of ethical measures, by applying qualitative coding and systems thinking. The essay illustrates how Buddhist ideas highlight structural interdependencies and encourage morally sound, flexible solutions. The end product is an integrative market facilitation roadmap that incorporates relational accountability, mindfulness, and non-harm into growth tactics. By redefining market participants as co-arising, interdependent agents, this method not only improves analytical depth but also promotes inclusive, long-lasting change. The study positions spiritual ideas as useful instruments in intricate market systems, which advances both development theory and the nascent area of Buddhist economics.